All-trans Retinoic Acid Overcomes Acquired Resistance to PLX4032 via Inhibition of PIN1 in Melanoma Cells - Kim, Garam; Bhattarai, Poshan Yugal; Oh, Chang-Hyun; Choi, Hong Seok (INT INST ANTICANCER RESEARCH, 2019)
Background/Aim: PLX4032 is commonly used in the treatment of advanced melanoma patients with BRAF-V600E mutation. The aim of this study was to elucidate the mechanisms by which up-regulation of PIN1 confers PLX4032 resistance in melanoma. Materials and Methods: The expression of PIN1 as well as the cytotoxic effects of combinatorial treatment of PLX4032 and all-trans retinoic acid (ATRA) were investigated by immunoblotting, MTT assay, TUNEL assay, and soft agar assay. Results: PIN1 expression is up-regulated in A375R cells, a PLX4032-resistant subline of melanoma cells generated from an A375 cell line, compared to parental A375 cells. Indeed, PIN1 positively regulated the expression of EGFR in A375R cells and led to activation of the RAF/MEK/ERK pathway. Importantly, PLX4032, when used in combination with ATRA, an inhibitor of PIN1, reduced EGFR expression, and consequently reduced cell viability and anchorage-independent growth of A375R cells compared to PLX4032 alone. Furthermore, co-treatment with ATRA and PLX4032 increased cleaved PARP and DNA fragmentation in A375R cells. Conclusion: PIN1 plays an important role in the development of PLX4032 resistance through up-regulation of EGFR expression.